HUBUNGAN PERSEPSI DAN EKSPEKTASI WISATAWAN TERHADAP PENGEMBANGAN PRODUK WISATA KASUS : BUKITTINGGI, SUMATERA BARAT - , Yesy Is ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Perception is the process of obtaining information about something from the surrounding environment, aiming very active to form cognition or thinking about the basic reality obtained and expectation is a desired hope of something positive to create a satisfaction. The purpose of this research is to formulate how the correaltion between the perception and expectations of the tourist toward tourism products (attractions, accessibilities, amenitas) in the city of Bukittinggi and the method used is quantitative descriptive research with the locus of Bukittinggi. The research findings are: (1) segmentation and characteristics of international tourist, (2) the perception of foreign tourists to the tourism product, (3) expectations of foreign tourists toward the tourism product, (4) the correlation between the perception and the expectations of tourists toward the tourism product in the city of Bukittinggi. The results of this study it can be concluded that based on the statistical analysis it was found significance which indicate that there was a significant correlation between perceptions and expectations. The more interesting the perception of tourists to the tourism product, the higher the expectations was. Keywords: perceptions, expectations, tourists and tourism product